Influence of weak magnetic fields treatment on photoluminescence of GaAs - Red'ko, S.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Long-term transformations in photoluminescence of GaAs single crystals treated with pulsed weak magnetic fields have been obtained. Treatments were performed in the multi-pulse (B = 60 mT, f = 10 Hz, τ = 1.2 ms, t = 5 min) regime. The defect structure transformations were inferred from the radiative recombination spectra within the range 0.6 to 2.5 μm at 300 and 77 K. A possible mechanism of the observed modifications related with electron-spin transformation is discussed.